PERILAKU KEWIRAUSAHAAN PEREMPUAN PENJUAL KULINER DI KOTA KENDARI - Hartini Hartini; Juharsah Juharsah (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2016)
This study aims to determine the entrepreneurial behavior of women culinary sellers in the city of Kendari. Informants in this research are women culinary seller in Kendari City which taken purposively. Data were collected through in-depth interviews and observations. The data collection was analyzed by descriptive qualitative method. The results show that women culinary sellers already have: relatively strong trust, tend to be task-oriented and result, business risk readiness is still not maximal, leadership is still relatively simple, and culinary originality produced is still relatively limited, and has a tendency to be oriented to the future.